Determinant of Bronchoarterial Ratio in a Patient Undergoing Computed Tomography Chest - Amrendra Kumar Mahato; Alina Khatiwada; Saurav Poudel; Sailendra Kumar Mahato; Dipak Kumar Yadav; Namrata Dev (Journal of Nobel Medical College, 2024)
Background: Respiratory diseases pose a significant challenge in Nepali clinical settings due to elevated smoking rates and environmental risks. This study explores the structural changes in conditions such as asthma, chronic obstructive pulmonary disease, and bronchiectasis, utilizing noninvasive multi-detector computed tomography to assess airway remodeling. Despite conflicting western literature on bronchoarterial ratios, this research emphasizes the importance of evaluating these ratios in the Nepalese context for predicting airway disease severity.